Ta‘līmu Ḥurūf al-Jarr wa-Asmā’ al-Ma‘rifah bi-Istikhdām Kitāb "Amṯilatī" fī al-Ma‘had al-Islāmī "Nūr al-‘Ilm wa al-Fikr" Tebuireng Jombang - Manisha Aulia; Fathurrohman; Siti Durotun Naseha (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2022)
This article examines the learning of the letters jer and isim ma'rifat using the amtsilati book at the Nurul Ilmi Wal Fikri Tebuireng Jombang Islamic Boarding School. This study aims to find out how the learning process, problems and solutions to problems when learning the letters jer and isim ma'rifat using the amtsilati book at the nurul ilmi wal fikri Islamic boarding school. This research uses descriptive qualitative research with the type of case study research. Data collection techniques by observation, interviews and documentation. The results of his research were the learning of the letters jer and isim marifat using the book of amtsilati, namely using the methods of discussion, dictation and question and answer. The teacher also reads out and explains the key points then the students imitate what the teacher reads. The learning process includes preamble, presentation of material and closing. The problem is that the Teacher does not motivate students in memorizing khulashoh amtsilati, different levels of understanding of students and improper timing. The solution to the problem is that students must learn as much as possible to make it easier in the learning process. Teacher  gave motivation and direction to be diligent in depositing the memorization of the nadhoman khulashoh. The holding of tiered classes. Changing the right learning hours and students must be able to maximize the existing time.